The Montreal Protocol: an international law achievement - Yépez Castro, José Alonso (2025)
The current state of the environment is a major concern for most of the countries. However, despite all the efforts made in the multilateral arena, it seems that the practical results are minimal. Within this context, the Montreal Protocol remains as an international instrument that has been implemented successfully worldwide. This article explores the legal characteristics that made the Montreal Protocol such a remarkable legal agreement, proposing that it involves a series of well-designed binding commitments, a precautionary approach, makes differentiation for developing countries, is a flexible agreement, does not include soft law, and reflects a sense of compromise among the international community, all of which has led it to its unquestionable success. For those purposes, the articles use an international law perspective mainly from the Critical Legal Studies approach and from Law and Economics.